Definition of Urban Park’ Concept Upon a Systemic, Management and Multidimensional Perspective - Sandoval-Chávez, Diego-Adiel; Vera, Edith; Reyes, Aida Yarira (Springer, 2024)
Within the realm of Engineering Management, this study aims to reframe the concept of urban park through its multidimensional construct since its essential nature of physical space and social interaction is persistently lost in most narratives. Conceptualizations follow from theory, but there are difficulties in eliciting the innocuous question of how to define Urban Parks. Hence, its scope belongs to the theoretical debates related to public space, social and managerial at large. From the intricacies of urban sociology, management science, and through the lens of system thinking, we argued about the urban park as a construct that implies a greater level and complexity that results from the fusion of simpler concepts. Thus, the interpretive paradigm of qualitative methods and critical literature review is the research design for our endeavor. We portray a systematic approach for a functional definition to study urban parks as an entropic, open, dynamic, and closed-loop system that triggers intricate processes and outcomes, which embeds a set of dimensions such a scaffolding strategy to support a conceptual framework into the spatial, scalar, urban, vegetal, social, intentional, multifunctionality, transcendence, symbolic, and dependence. We critically render an intentional but unique concept of urban park, in addition to concluding remarks aimed to reorient attention toward the relevance of public space in the study of Engineering Management and Urban Science.